Synthesis and Photo- and Ionochromic and Spectral-Luminescent Properties of 5-Phenylpyrazolidin-3-one Azomethine Imines. (23rd September 2018) - Bren, Vladimir A.; Dubonosov, Alexander D.; Popova, Oksana S.; Revinskii, Yurii V.; Tikhomirova, Karina S.; Minkin, Vladimir I.
Abstract : Photochromic 5-phenylpyrazolidin-3-one-based azomethine imines containing 2-((1 H -imidazol-2-yl)methylene)1, 2-(pyridin-2-ylmethylene)2, 2-(quinolin-2-ylmethylene)3, and 2-((8-hydroxyquinolin-2-yl)methylene)4 substituents were synthesized. All the compounds exist in the ring-opened O forms. Under irradiation with light of 365 nm, compounds1 –4 undergo thermally reversible isomerization into ring-closed bicyclic diaziridine isomers C. Azomethine imines1 –3 exhibit properties of ion-active molecular "off-on" switches of fluorescence when interacting with F − or AcO − anions. Compound4 represents a bifunctional chemosensor demonstrating a colorimetric "naked-eye" effect for Ni 2+ cation and complete fluorescence quenching in the presence of H +, F −, and CN − ions.